Community paralegals and the pursuit of justice - Gauri, Varun, 1966-; Maru, Vivek (Cambridge, United Kingdom ; New York, NY, USA : Cambridge University Press, 2018)
"In this book, we aim to characterize and assess a lesser-known intermediate institution-the community paralegal. According to the 2012 Kampala Declaration on Community Paralegals, community paralegals "use knowledge of law and government and tools like mediation, organizing, education, and advocacy to [help people] seek concrete solutions to instances of injustice." Paralegals and their clients typically address three kinds of problems: disputes among citizens, citizen grievances against state institutions, and disputes between citizens and private firms"--
Paralegal in Comparative Perspective : What Have We Learned Across These Six Countries? / Vivek Maru and Varun Gauri -- "To Whom do the People Take Their Issues?" : The Contribution of Community-Based Paralegals to Access to Justice in South Africa / Jackie Dugard and Katherine Drage -- Community-Based Paralegalism in the Philippines : From Social Movements to Democratization / Jennifer Franco, Hector Soliman, and Maria Roda Cisnero -- Paralegalism in Indonesia : Balancing Relationships in the Shadow of the Law / Ward Berenschot and Taufik Rinaldi -- Kenya's Community-based Paralegals : A Tradition of Grassroots Legal Activism / H. Abigail Moy -- Squeezing Justice Out of a Broken System : Community Paralegals in Sierra Leone / Vivek Maru, Lyttelton Braima, and Gibrill Jalloh -- The Contributions of Community-based Paralegals in Delivering Access to Justice in Post-war Liberia / Peter Chapman and Chelsea Payne.
Includes bibliographical references and index.
Keywords: Legal services -- Developing countries; Legal assistants -- Developing countries; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; Kampala Declaration on Community Paralegals